Understanding and Managing Corporate Brands: A System Dynamics Perspective - Dunnion, B; Knox, Simon (Cranfield University, 2004)
Corporate brands are shrouded in a “fog of complexity” (Balmer, 2001). While complexity, as a defining characteristic of corporate brands, cannot be legitimately avoided this, we suggest, is not true of the fog. A focus on constituent elements, indicative of reductionism, is evident in much corporate brand theorising. Because corporate brands consist of connected elements, whose interactions shape outcomes, they are complex systems. It is characteristic of complex systems that they not reducible to their constituent elements. So we suggest that, with corporate brands, the totality of the system must be properly understood to be effectively managed (Hatch, 1997). We argue that System Dynamics, previously unexplored in corporate brand theory, provides the holistic approach called for in the literature (King, 1991; Hatch and Schultz, 1997; Maklan and Knox, 1997). We take the view that corporate brands result from the actions, and interactions, of many actors and that the mental models of actors, in social systems, are determinants of their actions (Forrester, 1975). By adopting a system dynamics perspective we can contribute to corporate brand theory and practice. We can model the interactions of elements, organization functions, and mental models involved in corporate branding. Such models can lead to the development of new knowledge (Simon, 1999) and can enable the translation of knowledge into action (Pfiffer and Sutton, 1999). We can navigate through the current corporate brand fog (Knox and Bickerton, 2003) and, by making cause and effect relationships explicit, change prevailing mental models and behavio
Keywords: complex system; corporate brand; mental model; organization; sense-making; system dynamics; systems theory